Effects of beta-hydroxy beta-methylbutyrate on power performance and indices of muscle damage and stress during high-intensity training - Hoffman, J. R.; Cooper, J.; Wendell, M.; Im, J.; Kang, J. (The Journal of Strength and Conditioning Research, 2004)
Twenty-six members of a collegiate football team were randomly assigned to either a supplement (S) (3 g of ß-hydroxy ß-methylbutyrate [HMB] per day) or placebo (P) group. Testing occurred before (PRE) and at the end of 10 days of preseason football training camp (POST). During each testing session, subjects performed an anaerobic power test, and blood samples were obtained for testosterone, cortisol, creatine kinase, and myoglobin analysis. No differences in anaerobic power were seen between PRE and POST in either group. Cortisol concentrations were significantly decreased from PRE (333 ± 81 nmol·L-1) to POST (246 ± 79 nmol·L-1), and a sixfold increase was seen in creatine kinase concentrations at POST. However, no significant differences between the groups were seen. No significant time or group effects were observed in testosterone or myoglobin concentrations. Results suggest that short duration HMB supplementation does not provide any ergogenic benefit in collegiate football players during preseason training camp.